NATIONAL QUALIFICATIONS SYSTEM IN RUSSIA - AN EPISTEMOLOGICAL PERSPECTIVE - A. A. Muravyeva; O. N. Oleynikova; N. M. Aksenova; E. M. Dorozhkin (Russian State Vocational Pedagogical University, 2019)
Introduction. The article offers an insight into an epistemological perspective of establishing the national qualifications system in Russia that is critical for creating a "market of qualifications in the country that would be adequate to the current context.The aim of the research was to examine the context and factors underpinning the formation and evolution of the structure of knowledge relating to the national qualification system in Russia.Methodology and research methods. The methods applied comprise a mixed-method approach that included: review and analysis of official documents, semi-structured background and individual interviews with key stakeholders (line ministries, experts from industry and qualifications awarding bodies etc.) and desk research.Results and scientific novelty. The performed analysis of documents and of research data has revealed that the process of generating and enhancing knowledge about the national qualifications system semantically and methodologically is in broad terms contingent on the needs and objectives of social and economic development, and in narrower terms - on the development of occupational standards that underpin the standards of vocational and higher education, as well as on the enhanced institutionalisation of employers' involvement in the training of personnel and in the search of effective mechanisms and instruments of independent assessment of qualifications.It also offers an insight into current key paradigmatic gaps in the NQF-related epistemology in Russia that account for the specificity of the observed state of play and for the key conceptual epistemological contradiction that has been identified by the authors as the opposition of and conflict between occupational and education qualifications. The authors propose ways out of the situation based on international practices in this area starting from aligning the terminology and conceptual approaches with international ones. The performed epistemological research and the conclusions made by the authors contribute to the national qualifications system discourse. It is stressed that core principles underpinning the development of the national qualifications system should be adapted to the social and economic and local factors.Practical significance. The material of the article can be used by policy-makers dealing with the NQS development and implementation of the NQS.